Prevalence of body image dissatisfaction and associated factors among high school adolescent in Hawassa city, Ethiopia - Zenebe Jebero; Amanuel Elias; Gemeda Billo; Mohammed Ayalew; Yonas Alemayehu; Fikre Moga (Heliyon)
Background: Adolescence is a period in which individuals are more concerned with their body image. However, little is known about the prevalence of body image dissatisfaction and its associated factors. Thus, this study aimed to assess the prevalence of body image dissatisfaction and associated factors among high school adolescents in Hawassa city in 2023. Methods: A school-based cross-sectional study was conducted among 421 participants from April 30 to May 30, 2023, in Hawassa City. A stratified sampling technique was employed to select the participants. A structured, self-administered questionnaire was used to collect the data. Anthropometric measurements of body mass and stature were taken. A logistic regression model was fitted and used to identify the factors associated with body image dissatisfaction, and P < 0.05 indicated statistical significance. Results: The prevalence of body image dissatisfaction was 18.5 % [95 % CI = 14.8–22.2 %]. Being overweight/obese [Adjusted Odds Ratio(AOR) = 7.8, 95 % CI = 2.58–23.83], engaging in a small amount of exercise [AOR = 3.66, 95 % CI = 1.34–10.0], having moderate depression [AOR = 3.6, 95 % CI = 1.25–10.40], having severe depression [AOR = 6.8, 95 % CI = 1.94–24.22], late age of adolescence [AOR = 1.9, 95 % CI = 1.07–3.39], and family pressure [AOR = 2.2, 95 % CI = 1.28–4.04] were associated factors. Conclusion and recommendations: Body image dissatisfaction among adolescents in Hawassa City is prevalent, influenced by factors such as obesity, depression, limited physical activity, age, and family pressure. To address this issue, a multi-sectoral approach is necessary. The federal Ministry of Health should prioritize initiatives promoting healthy living, physical activity, and media awareness. The Public Health Authority should collaborate with families for healthier lifestyles, while schools and youth centers should implement educational programs to foster positive body image. Parents should model healthy body image behaviors and avoid negative comments. Comprehensive strategies are essential to address obesity, depression, and promote physical activity. This includes encouraging adolescents to engage in regular exercise and providing supportive family feedback.